Determinantes do preço de venda da cera de carnaúba beneficiada - Azevedo, Pedro Mapurunga (2010)
At this article, it was analyzed the real capacity of some valuation in a sales price of composition in a Carnauba Wax and it was tried to preview this price, the linear model that has been used was Least Quarters. Despite of ad hoc, the studied model and chosen variables have showed satisfactory results, it has been chosen macroeconomics variables, weathers variables (dummy) and specifics variables. The final results confirmed some empiric affirmations however it showed some results that business men from its market used to say the other way round.